Prioritizing factors affecting traffic volume of public-private partnership infrastructure projects - Nguyen, Phong Thanh; Likhitruangsilp, Veerasak; Onishi, Masamitsu (International Journal of Engineering and Technology, 2018)
Public-private partnership (PPP) is an effective alternative for raising capital for infrastructure projects and has been a popular trend in de-veloping countries recently. A key factor that affects the success of PPP transportation projects is traffic demand because it directly influ-ences project revenue. Inaccurate traffic demand estimates may lead to financial difficulties for private partners. This paper applies fuzzy extended analytic method (FEAM) to prioritize critical factors that affect traffic volume of PPP infrastructure projects. The results benefit both public and private sectors for realizing key factors for the success of PPP infrastructure project implementation.